Uji Aktivitas Antibakteri Pseudomonas Aeruginosa Pada Param Karo Sebagai Antidiabetic foot - ARDHANA, RANIA RARA (Jurnal Penelitian Farmasi Dan Herbal, 2025)
Param Karo is a traditional medicinal herb that is added with rice flour (Oryza sativa) as a solidifier. Param Karo has many properties, especially as an alternative treatment for fever, flatulence, and various other conditions. Param Karo is used by repeatedly applying it on the body to help normalize body temperature. The purpose of this study was to determine the activity of param Karo against Pseudomonas aeruginosa bacteria as the cause of diabetic foot wounds, as well as to identify the optimal concentration of param Karo needed to achieve significant antibacterial activity. Extraction was carried out using 96% ethanol solvent, and antibacterial activity testing was carried out by disc diffusion method on Pseudomonas aeruginosa bacteria with 3 concentrations namely, 25%, 50%, 75%. The results showed that the ethanol extract of Param Karo had the most significant antibacterial activity at a concentration of 75% with the formation of a clear zone around the disc. Ciprofloxacin was used as positive control, while DMSO 10% as negative control.